Biofeedback: Infant asthma - L. P. Rodríguez; J. J. Nombela; J. Ponce (Asociación Española de Ciencias del Deporte, 2010)
The present study is a revision of the different applications of biofeedback in infantile bronchial asthma. The technique may be used on its own (preferably in the motor area) or in conjunction with other techniques such as hypnosis, relaxation, etc. However, it should be stated that previous work published in this field is difficult to interpret since results are inconclusive, it is, therefore, difficult to produce a scientific summary. KEY WORDS: Biofeedback; infantile asthma; respiratory biofeedback.